Off-shore structures proceedings of the conference held in London, 7-8 October 1974. (Thomas Telford for the Institution of Civil Engineers, 1975)
Sir William Harris provides the opening address in this book focusing on off-shore structures. Topics covered by the 15 papers include the environment, soil mechanics of the seabed, concrete structures, dynamics of off-shore structures, risk factors involved and research requirements. Preceding the closing address state of the art operations are discussed.